Determination of side products in the photocatalytic generation of hydrogen with copper photosensitizers by resonance Raman spectroelectrochemistry. Issue 107 (7th November 2016) - Zhang, Ying; Heberle, Martin; Wächtler, Maria; Karnahl, Michael; Dietzek, Benjamin
Abstract : A combination of UV-Vis, resonance Raman spectroscopy and electrochemistry is employed to reveal the nature of a side product when using heteroleptic Cu(i )-photosensitizers for photocatalytic hydrogen production. Abstract : A combination of UV-Vis and resonance Raman spectroscopy in conjunction with electrochemistry is employed to reveal the nature of a side product formed when using heteroleptic Cu(i )-photosensitizers [(P^P)Cu(N^N)] + for photocatalytic hydrogen generation. It is shown that homoleptic [Cu(N^N)2 ] + complexes are formed under oxidative conditions confirming a proposed deactivation pathway.